2009
DOI: 10.1007/s11145-009-9179-5
|View full text |Cite
|
Sign up to set email alerts
|

Reading interventions for struggling readers in the upper elementary grades: a synthesis of 20 years of research

Abstract: A synthesis of the extant research on reading interventions for students with reading difficulties and disabilities in fourth and fifth grade (ages 9-11) is presented. Thirteen studies with treatment/ comparison study designs and eleven single group or single subject studies were located and synthesized. Findings from the 24 studies revealed high effects for comprehension interventions on researcher-developed comprehension measures. Word recognition interventions yielded small to moderate effects on a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
182
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(201 citation statements)
references
References 37 publications
13
182
2
4
Order By: Relevance
“…This is particularly alarming when we consider that in the United States, for example, the Census Bureau reported that out of 3.9 million eighth graders who took the National Assessment of Educational Progress (NAEP) in 2007, twenty-six percent 'did not attain basic levels of literacy, and only 31% reached proficiencymeaning that roughly 1 million eighth graders were stalled at basic literacy levels and another 1.7 million were not proficient' (Greenleaf & Hinchman, 2009, p5). Further research has suggested that for many of these young people, difficulties with reading have plagued them since their early years in school (Wanzek, Wexler, Vaughn, & Ciullo, 2010). Hall (2016, p. 56) therefore warns that as a result of this constant 'failure', 'these students may refrain from engaging in classroom reading practices because of the belief that they cannot succeed, have little to offer, and cannot change their situation'.…”
Section: Ijep -International Journal Of Educational Psychology 7(2) 125mentioning
confidence: 99%
“…This is particularly alarming when we consider that in the United States, for example, the Census Bureau reported that out of 3.9 million eighth graders who took the National Assessment of Educational Progress (NAEP) in 2007, twenty-six percent 'did not attain basic levels of literacy, and only 31% reached proficiencymeaning that roughly 1 million eighth graders were stalled at basic literacy levels and another 1.7 million were not proficient' (Greenleaf & Hinchman, 2009, p5). Further research has suggested that for many of these young people, difficulties with reading have plagued them since their early years in school (Wanzek, Wexler, Vaughn, & Ciullo, 2010). Hall (2016, p. 56) therefore warns that as a result of this constant 'failure', 'these students may refrain from engaging in classroom reading practices because of the belief that they cannot succeed, have little to offer, and cannot change their situation'.…”
Section: Ijep -International Journal Of Educational Psychology 7(2) 125mentioning
confidence: 99%
“…Ces derniers sont considérés par les auteurs comme ayant des besoins similaires à ceux du début du secondaire. Wansek et al (2010) ont recensé 24 recherches dont les participants avaient principalement entre 9 et 11 ans et étaient décrits comme de faibles lecteurs sans toutefois avoir un diagnostic précis. Leur analyse montre des effets d'ampleur modérés à grands lorsque les interventions portent sur le vocabulaire et les stratégies de compréhension en lecture.…”
Section: Les Recherches Sur L'enseignement De La Lecture Et L'apportunclassified
“…Plusieurs auteurs soulignent les difficultés rencontrées lorsqu'ils tentent d'analyser des résultats de recherches tantôt relatifs à des évaluations construites par les chercheurs, tantôt à des évaluations normatives (Kaldenberg et al, 2015;Scammacca et al, 2015;Wansek et al, 2010). Cela rend difficile la comparaison entre les études ; il s'avère laborieux de préciser les interventions utiles à l'élève et leur incidence sur l'apprentissage.…”
Section: L'analyse De Recensions Antérieures Période De 2012 à 2016unclassified
See 1 more Smart Citation
“…For students with reading difficulties and disabilities, reading fluency is often more challenging; reading sight words and decoding novel words is slow and arduous, making text comprehension difficult (Chard et al 2002;Kim 2000;Kim and Park 2015). Due to the critical role of fluency as a predictor for successful reading, researchers have provided numerous suggestions for instructional practices for teachers to promote students' fluency in classrooms (e.g., Therrien 2004), as well as specialized recommendations for teaching fluency to struggling readers and students with disabilities (e.g., Chard et al 2002;Wanzek et al 2010;Wexler et al 2008).…”
Section: Introductionmentioning
confidence: 99%